FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KADAR HEMOGLOBIN (Hb) PASIEN HEMODIALISIS; STUDI PENDAHULUAN - Erika Nurwidiyanti; Afrida, Maryudella (Jurnal Kesehatan, 2021)
Background: Chronic kidney disease (CKD) occurs due to decrease a progressive and irreversible in kidney function, which requires life-long replacement therapy for renal function. Anemia is one of the effects due to decreased kidney function, a diet that is too strict, and a result of the dialysis process. This is of course a concern for health workers to maintain the quality of life for patients. Objectives: To determine the relationship between age, gender, nutritional status, duration of hemodialysis, and dialysis adequacy with hemoglobin levels in hemodialysis patients. Research method: This research design is descriptive correlation with a total sample of 65 respondents taken by random sampling with random number technique. The research instrument used a questionnaire and a sheet of the measurement of nutritional status, dialysis adequacy, and hemoglobin levels. Results: The results showed that there was a relationship between the length of time undergoing hemodialysis and hemoglobin levels in hemodialysis patients with p-value of 0.036. While, age, gender, nutritional status and dialysis adequacy were not related to the patient's hemoglobin level (p-value > 0.05). This can be influenced by the patient's quality of life and good management of anemia in the patient. Conclusion: The results showed that the longer the patient underwent hemodialysis, the hemoglobin level was better, so it was important for nurses to make appropriate interventions so that the patient's hemoglobin level could be maintained and had an impact on the patient's quality of life.